Digitalización de la técnica EIS-FRA como respuesta al problema de multisensado simultáneo y portabilidad - Sánchez González, Arturo; Medrano, Nicolás; Calvo, Belén (Jornada de Jóvenes Investigadores del I3A, 2019)
A new fully digital approach to classically analogical design of Electrochemical Impedance Spectroscopy (EIS) by Frequency Response Analyzer (FRA) methods is presented in this work. The proposed system relies in a commercial low-cost multicore processor as the only active element, achieving high technical specifications and multisensing capabilities without compromising consumption, portability or miniaturization.